THE EFFECT OF OXYTOCIN TREATMENT ON THE ADULT LIVER OF STREPTOZOTOCIN (STZ) - INDUCED DIABETIC RATS - (:unkn) unknown (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2017)
Diabetes is a factor that causes hepatic damage. This experimental study has been designed to investigate possible therapeutical and protective effects of oxytocin in streptozotocin-(STZ) induced diabetes. Wistar albino rats used in this study were randomly divided into four groups: I) Control Group, II) STZ induced Diabetic Group (STZ Group), III) Diabetic Group with Pre-Oxytocin treatment (Pre-Oxytocin Group) and IV) Diabetic Group with Post-Oxytocin treatment (Post-Oxytocin Group). Rats with blood glucose levels of 200 mg/dL or higher were considered to be diabetic and included in the study. At the end of the 4th week, hepatic tissue samples were taken to be processed for light microscopy. Blood samples were determined for Malondialdehyde (MDA), glutathione (GSH) and Advanced Oxidation Protein Products (AOPP) measurements. The histopathological damage score of hepatic tissue, which was significantly increased in the STZ group, was decreased by oxytocin treatment. According to biochemical data, MDA and AOPP levels were reduced, whereas GSH level was increased in oxytocin-treated groups when compared to STZ group. The present study demonstrates that oxytociri pretreatment reduced the degree of hepatic injury by providing a cellular protection against oxidative stress produced by STZ-induced diabetes mellitus.
Keywords: Experimental diabetes; liver; oxytocin; oxidative stress; OXIDATIVE STRESS; ACID; EXPRESSION; MELATONIN; DAMAGE; MODEL